The usage of e-cigarette in curbing tobacco addiction: a baseline study - Haziq Zailani; Abdul Rahman Ahmad Badayai (Penerbit Universiti Kebangsaan Malaysia, 2020)
Tobacco cigarette is not the only product that consist of nicotine as the existence of electronic cigarette had been observed as a device that can replace the function of a tobacco cigarette. However, electronic cigarette has caused many controversial issues, especially as an intervention for tobacco cigarette's cessation. For that reason, this study was conducted as the baseline study to find the effectiveness of electronic cigarettes in curbing the tobacco cigarette's addiction and the existence of dual-use. Ten subjects went through the screening test, using the Fagerstrom Test for Nicotine Dependence (FTND) to join this experiment for 40 days. The research used to pretest and posttest design. The baseline results showed that the electronic cigarette is effective in curbing tobacco cigarette addiction as the percentage of the consumed tobacco cigarette was decreased; 87.93% on min value to 35.38% on the maximum value. The existence of dual-use also has been proved. In which, all subjects showed an increase in the usage of an electronic cigarette. Despite the usage of tobacco, cigarettes decreased. Moreover, the baseline results showed that the dependence of nicotine is also decreased significantly (t = 22.481, p < 0.05) in paired t-test.